Analisis Pendapatan dan Kesejahteraan Petani Karet Di Desa Sari Mulya Kabupaten Tanah Bumbu - Fitriyana; Rizali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted with the aim of analyzing the income and welfare ofrubber farmers in Sari Mulya village, Sungai Loban District, Tanah Bumbu Regency. Thenumber of respondents in this study were 67 samples. And this research uses descriptivequantitative methodThe results of this study indicate that the average income of rubber farmers in thevillage of Sari Mulya sub-district Sungai Loban Regency Tanah Bumbu is Rp.3,761,726. andfor the level of prosperity the rubber farmers in the village of Sari Mulya belong to theprosperous farmers.